Transitional justice and aid - Sirkku K. Hellsten (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper examines the current security-governance-development nexus, something that is often also discussed under the concept of transitional justice (TJ). The paper analyses how the ambiguous, evolving and expanding nature of the concept of TJ affects the planning, coordination, evaluation and assessment of aid given to conflict ridden, post-conflict or (post) authoritarian societies in order to strengthen their democracy. Special attention is paid to gender justice. Illustrations are drawn mainly from Africa where many TJ processes and mechanisms are currently taking place.
Keywords: F5; O2; I3; 330; transitional justice; post-conflict reconstruction; development; social justice; human rights; development aid